2016
DOI: 10.1016/j.orcp.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy outcomes of overweight and obese women aged 35 years or older – A registry-based study in Finland

Abstract: SummaryObjective: To compare pregnancy outcomes of overweight and obese pregnant women aged 35 years or older to women aged less than 35 years old. Methods: A registry-based study covering years 2004-2008 including data on women ≥35 years (N = 45,718) compared to those <35 years (N = 203,930) and their prepregnancy body mass index (BMI) (<25, 25-29 and ≥30). In multivariable modelling, the main outcome measures were preterm delivery (<28 weeks, 28-31weeks and 32-36 weeks), low Apgar scores at 5 min, small-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 25 publications
(18 reference statements)
4
38
2
1
Order By: Relevance
“…In this meta-analysis, studies with OR adjusted to previous c-section and previous PP showed a greater magnitude of association with PP (35)(36)(37)(38)(39) 4.36, 95%CI: 3.08-6.17) compared to those that were not adjusted. This finding shows that, when logistic regression is made and adjusted for important factors, one gets closer to the actual contribution of old age to the outcome of PP.…”
Section: Figurementioning
confidence: 68%
See 1 more Smart Citation
“…In this meta-analysis, studies with OR adjusted to previous c-section and previous PP showed a greater magnitude of association with PP (35)(36)(37)(38)(39) 4.36, 95%CI: 3.08-6.17) compared to those that were not adjusted. This finding shows that, when logistic regression is made and adjusted for important factors, one gets closer to the actual contribution of old age to the outcome of PP.…”
Section: Figurementioning
confidence: 68%
“…We considered 35 years or older as the cutoff point for separation between young and older women. Most articles subdivided advanced maternal age into 35-39 years and ≥ 40 years 10,11,12,13,14,15,16,19,20,33,34,35 , others used ≥ 35 years 21,25,36,37,38,39,40 , and some only considered AMA age ≥ 40 years 41,42,43,44 . Regarding the definition of the age range for the comparison group, the studies were very different, with most using 20 to 34 years (30.4%), followed by < 35 years (21.1%), 25 to 29 years (17.4%), and others (26.1%).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 20 articles (19 cohort studies and 1 case–control studies) involving 2 153 898 participants were included in this meta‐analysis. For obesity (including all obesity classes), 16 articles (15 cohort studies and 1 case–control studies) involving 1 308 888 participants met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…However, the conclusions of several epidemiological studies are inconsistent with regard to a link between obesity and shoulder dystocia. Three studies link shoulder dystocia with obesity but another three do not substantiate the link.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, in univariate analysis, we found that smoking until birth was associated with advanced maternal age (Table 3). Pregnant women aged older than 35 years are considered to be at a higher risk for adverse perinatal outcomes (12,13). Smoking during pregnancy for this age group could add burden and worsen adverse perinatal outcomes (11).…”
Section: Discussionmentioning
confidence: 99%